A Discrete PLL based Load Frequency Control of FLC-based PV-wind Hybrid Power System with Real Time Data - A. V. Pavan Kumar; Alivelu M. Parimi; K. Uma Rao (Institute of Advanced Engineering and Science, 2016)
The sun and wind based generation are considered to be alternate source of green power generation which can mitigate the power demand issues. As solar and wind power advancements are entrenched and the infiltration of these Renewable Energy Sources (RES) into to network is expanding dynamically, testing errand is to keep up the voltage and frequency of the power generated from RES consistent as they specifically relies upon environmental conditions. So, as to outline a legitimate control and to harness power from RES the learning of natural conditions for a specific area is fundamental. With this fundamental information of the environmental conditions, a suitable Photovoltaic and Wind power generations is selected to generate clean and green electricity. Fuzzy Logic Controller (FLC) based Maximum Power Point Tracking (MPPT) controlled boost converter are utilized for viable operation and to keep DC voltage steady at desired level. The control scheme of the inverter is intended to keep the load voltage and frequency of the AC supply at constant level regardless of progress in natural conditions and burden. A Simulink model of the proposed Hybrid system with the MPPT controlled Boost converters and Voltage regulated Inverter for stand-alone application is developed in MATLAB R2015a, Version 8.5.0. The ongoing information of Wind Speed and Solar Irradiation levels are recorded at BITS-Pilani, Hyderabad Campus utilizing climate observing framework introduced at the area the performance of the voltage regulated inverter under constant and varying linear AC load with the real time data of the solar irradiation and wind speed as input is analyzed. The investigation shows that the magnitude of load voltage and frequency of the load voltage is maintained at desired level by the proposed inverter control logic.